Feasibility Study of Franchise Business Model In Indian Environment: Exploring Franchise Opportunities and Challenges in India's Growing Market (Journal of Advances and Scholarly Researches in Allied Education, 2013)
An comprehensive study of over 80 franchisees across thecountry assisted us to recognize the possibilities and difficulties of anbusiness owner having a franchisee. This report is an important piece ofinformation on the current styles of franchising in Native India. We wish toshow deep sense of appreciation to the franchisees of prestigious brand like PTeducation for their opinions, encounters and useful recommendations, whichassisted us in achieving this task with excellence. India, with a huge customerpopulation with continous economic growth becomes interesting location for thefranchising fraternity. Thus India has offered excellent possibilities to thenew worldwide and local manufacturers coming into the market with thepossibilities of growing their business.